PENGARUH INSIDER OWNERSHIP, INSTITUTIONAL OWNERSHIP DAN FREE CASH FLOW TERHADAP DIVIDEND PAYOUT RATIO DAN STOCK PRICE - Irnanta, Hesti; Darminto, Darminto; Arifin, Zainul (Profit: Jurnal Adminsitrasi Bisnis, 2014)
The manufacturing companies ability in facing the economic fluctuation finally influence the policy making, including dividend policy. Beside that the ownership composition of manufacturing companies in Indonesia still centralized that is mostly dominated by institution, make research to investigate the agency relation in the developed countries where the stock ownership is spread  and not centralized as in Indonesia. At the manufacturing companies that listed at Indonesian Stock Exchange only few stockholders that have initiative and ability to control and monitor the management decision  and activities, then the agencies will emerge so the dividend become important that influence the company stocks price. Based on the explanation above, then the manufacturing companies were selected to be objects in the research. The research is explanatory research, explained the causal relation among researched variables through hypothesis testing. The researched samples were 12 manufacturing companies. Data analysis by path analysis. Result of the research 1) the insider ownership directly not influence the dividend payout ratio 2)  institutional ownership directly influence the dividend payout ratio 3) free cash flow directly influence dividend payout ratio 4) insider ownership directly influence the stock price 5) institutional ownership directly influence the stock price 6) free cash flow directly influence the stock  price 7) dividend payout ratio directly influence the stock price 8) insider ownership significant indirectly trought its influence on stock price dividend pay out ratio 9) institutional ownership significant indirectly trought its influence on stock price dividend pay out ratio 10) free cash flow significant indirectly trought its influence on stock price dividend pay out ratio.   Keywords: insider ownership, institutional ownership, free cash flow, dividend payout ratio, and stock price. Kemampuan perusahaan manufaktur dalam menghadapai fluktuasi ekonomi pada akhirnya berimbas dalam pembuatan kebijakan, termasuk kebijakan dividen. Selain itu, komposisi kepemilikan saham perusahaan manufaktur di Indonesia yang masih terpusat yaitu banyak dikuasai oleh institusi, membuat penelitian untuk meneliti hubungan agency di perusahaan manufaktur menjadi menarik. Hal ini dikarenakan teori agensi dibangmaju dimana kepemilikan sahamnya bersifat menyebar dan tidak terpusat seperti di Indonesia. Pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia hanya ada beberapa pemegang saham saja yang mempunyai insentif dan kemampuan untuk mengontrol dan memonitor keputusan dan aktivitas manajemen, maka masalah agensi akan muncul sehingga dividen menjadi penting yang kemudian akan berpengaruh terhadap harga saham perusahaan. Berdasarkan uraian tersebut, maka perusahaan manufaktur dipilih untuk menjadi objek dalam penelitian ini. Penelitian ini dilakukan dengan menggunakan Explanatory Research, yaitu menjelaskan hubungan kausal antara variabel-variabel penelitian melalui pengujian hipotesa. Jumlah sampel yang diteliti adalah 12 Perusahaan manufaktur. Analisis data yang digunakan adalah Path Analysis. Hasil penelitian ini adalah 1) Insider Ownership secara langsung  tidak signifikan pengaruhnya terhadap Dividend Payout Ratio 2) Institutional Ownership secara langsung signifikan pengaruhnya terhadap Dividend Payout Ratio. 3) Free Cash Flow secara langsung signifikan pengaruhnya terhadap Dividend Payout Ratio. 4) Insider Ownership Secara langsung signifikan pengaruhnya terhadap Stock Price. 5) Institutional Ownership secara langsung signifikan pengaruhnya terhadap Stock Price 6) Free Cash Flow secara langsung signifikan pengaruhnya terhadap Stock Price. 7) Dividend Payout Ratio secara langsung signifikan pengaruhnya terhadap Stock Price. 8) Insider Ownership secara tidak langsung signifikan pengaruhnya terhadap Stock Price melalui Dividend Payout Ratio. 9) Institutional ownership secara tidak langsung signifikan pengaruhnya terhadap Stock Price melalui Dividend Payout Ratio 10) Free Cash Flow secara tidak langsung signifikan pengaruhnya terhadap Stock Price melalui Dividend Payout Ratio. Kata Kunci : Insider Ownership, Institutional Ownership, Free Cash Flow, Dividend Payout Ratio, dan Stock Price.